MERAWAT PANCASILA DI NEGERI SYARIAT ISLAM - Triyanto Triyanto; Yeni Sri Lestari; Irma Juraida; Rahma Husna Yana (Jurnal Community, 2019)
There has been a lot of attention on the implementation of Islamic Sharia in Aceh, and some have even linked it to human rights violations. The most important thing for Indonesian citizens is that the implementation of Islamic law can be regarded as a denial of the Pancasila as the basis of the state which has played a close role in binding Indonesian unity. If Jakarta has permitted the implementation of Islamic Sharia in Aceh, then how do Acehnese citizens take care of Pancasila? The research data shows that the implementation of Islamic Sharia does not violate Pancasila but precisely the actual implementation of the first principle of Pancasila. To that end, caring for Pancasila requires many community leaders in rural areas such as the older generation who still view the importance of Pancasila as the basis of the state, given the many differences that exist in Indonesian society. In addition to these community leaders, the socialization carried out by the regional government must choose people who are truly capable of transforming their understanding of the harmony of Islamic Sharia with Pancasila and not merely ceremonial socialization that only stops with people or figures and formal officials who have never fight for the existence of Pancasila in Aceh.